Comparison of surgical outcomes of C1-2 fusion surgery between O-arm-assisted operation and C-arm assisted operation in children with atlantoaxial rotatory fixation - Zhou, Xin; Yang, Yue Benny; Meng, Yichen; Lin, Tao; Zhou, Xuhui; Wang, Ce (Frontiers in Pediatrics, 2023)
Objective: The purpose of the present study was to compare surgical outcomes between C-arm fluoroscopy and O-arm navigated pedicle screw placement in the treatment of atlantoaxial rotatory fixation in children Methods: We retrospectively evaluated a total of 85 children with atlantoaxial rotatory fixation who underwent C-arm fluoroscopy (46 patients) or O-arm navigated pedicle screw placement (39 patients) from April 2014 to December 2020. Outcomes including operative time, estimated blood loss (EBL), accuracy of screw placement (Neo's classification), reduction rate of the atlantoaxial joint, and completed fusion time were evaluated. Results: A total of 340 screws were placed in 85 patients. The accuracy of screw placement of the O-arm group was 97.4%, which was significantly higher than that of the C-arm group (91.8%). The O-arm group (reduction rate 100%) had a higher atlantoaxial joint reduction rate than the C-arm group (reduction rate 93.5%). Statistical significance (230.0±34.6 mL vs. 150.6±47.3 mL, p < 0.05) was observed with respect to the median blood loss between the C group and the O group. There were no statistically significant difference (122.0±16.5 minutes vs. 110.0±14.4 minutes, p=0.604) with respect to the median operative time in the C group and in the O group. Conclusions: O-arm-assisted navigation allowed more accurate screw placement, better reduction, and less intraoperative blood loss. Both groups had satisfied bony fusion at 6 months of follow-up. O-arm navigation did not prolong the operative time despite the time required for setting and scanning, and radiation exposure was within an acceptable range.